(untitled) (Journal of Health, Population and Nutrition, 2009)
Health services and modern medicines are out of reach for over one billion people globally. Micro-insurance for health is one method to address unmet health needs. This case study used a social exclusion perspective to assess the health and poverty impact of micro-insurance for health in Bangladesh and contrasts this with several micro-insurance systems for health offered in India. Micro-insurance for health in Bangladesh targeted towards the poor and the ultra-poor provides basic healthcare at an affordable rate whereas the Indian micro-insurance schemes for health have been implemented across larger populations and include high-cost and low-frequency events. Results of analysis of the existing literature showed that micro-insurance for health as currently offered in Bangladesh increased access to, and use of, basic health services among excluded populations but did not reduce the likelihood that essential health-related costs would be a catastrophic expense for a marginalized household. Key words: Health expenditure; Health insurance; Microcredit; Microfinance; Micro-insurance; Poverty; Rural health services; Bangladesh doi: 10.3329/jhpn.v27i4.3402 J Health Popul Nutr 2009 Aug;27(4):563-573